Teori Naskh Wa Mansukh Dalam Al-Qur’an - Alfazri Alfazri (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2023)
This journal talks about the Naskh wa Mansukh theory, this naskh theory still leaves comparisons between groups of scholars. Because of that, there are some scholars who accept the naskh theory and some do not. The difference in opinion of these scholars can be seen from the determination of the terminology of texts from classical times to contemporary times. Manna Kholil al-Qattan explains in his book Mabahits fi 'Ulum al-Qur'an, that what is meant by nasikh is the abolition of a Shari'a law with another Shari'a law, but he excludes this abolition by reason of death or madness. Ulama who reject naskh on the grounds that naskh is a law that has clear provisions and cannot be revoked. Furthermore, there are scholars who recognize Naskh with arguments based on the word of Allah SWT QS. al-Baqarah verse 106.